A kind of PET polyester and its preparation method and application
By using specific metal salt additives to control the melt crystallization process of PET polyester during the PET polymerization process, the problem of insufficient crystallization saturation of PET resin is solved, and better processing and molding effect and material performance are achieved.
Patent Information
- Application Number
- CN202510003246.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to significantly improve the crystal saturation of PET resins, resulting in poor processing and molding effects, and problems with dimensional stability, mechanical strength and surface smoothness.
The melt crystallization process of the polyester is controlled to achieve saturated crystallinity by using terephthalic acid, ethylene glycol, catalysts and metal salts (such as phosphonate, sulfite and amine acetate) as raw materials.
The saturated crystallinity of PET polyester is achieved, the processing and forming effect is improved, and the problems of dimensional stability, mechanical strength and surface smoothness are solved.
Smart Images

Figure CN119751831A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical production, and in particular to PET polyester and a preparation method and application thereof. Background Art
[0002] Polyethylene terephthalate (PET) is one of the five general-purpose plastics. The rigid benzene ring in the repeating unit of its molecular chain brings high tensile strength, good heat resistance, creep resistance, chemical resistance and wear resistance, and the methylene group brings crystallinity. Its excellent comprehensive performance makes it widely used in the fields of fiber, film, bottle packaging, etc. PET is a semi-crystalline resin material. The conventional PET crystallization rate is slow and its use in engineering plastics is limited. Many researchers focus on using inorganic compounds, organic compounds or polymers to improve the crystallization rate of PET to increase the crystallization rate and shorten the demolding cycle.
[0003] However, while developing fast crystallization PET, no relevant research on PET saturated crystallization has been seen. In addition to the crystallization rate, the saturation of crystallization is equally important for PET materials. The excess amorphous region inside the unsaturated crystallization PET resin will cause dimensional stability problems, product surface smoothness problems and mechanical strength problems. In the study of PET rapid crystallization process, relevant nucleating agents were added, and it was found that after the crystallization rate increased, the polyester still had a secondary crystallization process after melt crystallization, which shows that the increase in the crystallization rate of PET resin did not improve its crystallization saturation.
[0004] Therefore, there is an urgent need to develop new methods for preparing PET to significantly improve the crystal saturation of PET resin.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a PET polyester and a preparation method and application thereof, aiming to saturate the crystallinity of the polyester so as to improve the processing and molding effect.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides a PET polyester obtained by polymerization using terephthalic acid, ethylene glycol, a catalyst and a metal salt as raw materials;
[0009] The metal salt is selected from at least one of phosphonate, sulfite and aminoacetate.
[0010] In an optional embodiment, in the total amount of terephthalic acid and ethylene glycol, the mass proportion of terephthalic acid is 57.3%-72.2%, and the mass proportion of ethylene glycol is 27.8%-42.7%;
[0011] Preferably, the amount of catalyst added is 10ppm-300ppm of the total amount of terephthalic acid and ethylene glycol;
[0012] Preferably, the added amount of the metal salt is 1 ppm to 500 ppm based on the mass of terephthalic acid.
[0013] In an optional embodiment, the metal salt is selected from at least one of sodium sulfite, sodium bisulfite, sodium thiosulfate, sodium polysulfate, potassium sulfite, tetrasodium ethylenediaminetetraacetate, disodium ethylenediaminetetraacetate, sodium nitrilotriacetate, diethylenetriamine pentacarboxylate, sodium hexametaphosphate, sodium triphosphate and bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid monoethyl ester) calcium;
[0014] Preferably, the metal salt is selected from at least one of sodium sulfite, tetrasodium ethylenediaminetetraacetate, disodium diaminetetraacetate, and calcium bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonate);
[0015] Preferably, when the metal salt is a phosphonate, the added amount is 20ppm-200ppm of the mass of terephthalic acid; when the metal salt is a sulfite, the added amount is 1ppm-50ppm of the mass of terephthalic acid; when the metal salt is an aminoacetate, the added amount is 5ppm-150ppm of the mass of terephthalic acid;
[0016] Preferably, the catalyst is selected from at least one of antimony glycol, antimony acetate, antimony trioxide and germanium oxide.
[0017] In an optional embodiment, the intrinsic viscosity of PET polyester is 0.9 dL / g-1.3 dL / g;
[0018] Preferably, the PET polyester is heated to 280-320°C to eliminate the thermal history, undergoes melt crystallization, and is heated again to melt in a melting process without a cold crystallization peak or with a small cold crystallization enthalpy; when a cold crystallization peak appears, the cold crystallization enthalpy is 0 J / g-3 J / g.
[0019] In a second aspect, the present invention provides a method for preparing PET polyester according to any one of the aforementioned embodiments, comprising: polymerizing terephthalic acid, ethylene glycol, a catalyst and a metal salt as raw materials, and then performing solid phase viscosity enhancement.
[0020] In an optional embodiment, the preparation process includes esterification reaction, prepolymerization reaction, polycondensation reaction and solid phase viscosity enhancement performed in sequence;
[0021] The metal salt is added before the esterification reaction or after the esterification reaction and before the prepolymerization reaction;
[0022] Preferably, the metal salt is mixed and dissolved with a solvent to obtain a metal salt solution before being added, and is added in the form of a metal salt solution; more preferably, the mass fraction of the metal salt in the metal salt solution is 0.01%-0.5%; more preferably, the solvent is selected from at least one of ethylene glycol and water.
[0023] In an optional embodiment, the esterification reaction comprises: mixing terephthalic acid, ethylene glycol and a catalyst for esterification reaction to obtain an esterified product;
[0024] The reaction temperature of the esterification reaction is 240°C-270°C, the esterification pressure is 90KPa-120KPa, the top temperature of the process tower is controlled to be 100°C-120°C, and the reaction time is 2h-3h.
[0025] In an optional embodiment, during the prepolymerization reaction, the reaction temperature is controlled to be 250°C-270°C, and the esterification pressure of the esterification reaction is controlled to gradually decrease to 3KPa-5KPa, and the time for the pressure drop is 50min-80min.
[0026] In an optional embodiment, the reaction temperature of the polycondensation reaction is 275°C-280°C, the reaction pressure is 10Pa-100Pa, and the reaction time is 1h-2h;
[0027] Preferably, after the polycondensation reaction is completed, the polyester chips are pelletized and dried to obtain polyester chips, and then the polyester chips are solid-phase thickened to make the intrinsic viscosity reach 0.9 dL / g-1.3 dL / g;
[0028] Preferably, the solid phase viscosity increasing process is carried out in a rotary drum solid phase viscosity increasing device, and the temperature of the solid phase viscosity increasing is controlled to be 220° C.-230° C., the pressure is 10 Pa-100 Pa, and the solid phase viscosity increasing time is 30 h-45 h.
[0029] In a third aspect, the present invention provides use of the PET polyester according to any one of the aforementioned embodiments or the PET polyester prepared by any one of the preparation methods according to the aforementioned embodiments in the preparation of plastic products.
[0030] The invention has the following beneficial effects: PET polyester is prepared by polymerization with terephthalic acid, ethylene glycol, a catalyst and a metal salt as raw materials, and the polyester is prepared by adding phosphonate salts, sulfites and aminoacetate compounds in the polymerization process of PET polyester by adding auxiliary agents. These metal salts have a certain complexing, stabilizing or reducing effect, which can inhibit or reduce the nucleation effect of the catalyst metal ions on the polyester chain segments on the one hand, and inhibit the side reactions catalyzed by the catalyst at high temperature on the other hand, thereby making the crystallization process more orderly and sufficient to a certain extent, so that the crystallinity reaches saturation. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 The melting crystallization curves of the polyester chips obtained in the examples and comparative examples are shown;
[0033] Figure 2 The following are the melting curves of the polyester chips obtained in the examples and comparative examples when they are heated again. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0035] The present invention is innovative in that the high-viscosity polyester still has the phenomenon of cold crystallization after melt crystallization, and achieves the saturated crystallinity of the high-viscosity polyester during the melt crystallization process by adding an auxiliary agent. This solves the problems of stability, mechanical strength or surface smoothness of the product, etc., which may lead to the potential shortening of the size of the high-viscosity polyester after processing.
[0036] The embodiment of the present invention provides a method for preparing PET polyester, wherein metal salts such as phosphonate, sulfite, aminoacetate, etc. are added during the polymerization process of polyester to prepare polyester, and terephthalic acid, ethylene glycol, a catalyst and a metal salt are used as raw materials for polymerization, and the steps are as follows:
[0037] S1. Prepare materials
[0038] Prepare terephthalic acid, ethylene glycol, a catalyst and a metal salt. The metal salt is selected from at least one of phosphonate salts, sulfites and aminoacetates. The metal salt can be any one or more of the above, and can be used as an additive in the synthesis of PET polyester to widen the melting crystallization temperature range, so that the polyester crystallinity can reach saturation, and it is easier to process and shape than unsaturated crystalline PET polyester.
[0039] In a preferred embodiment, the metal salt is selected from at least one of sodium sulfite, sodium bisulfite, sodium thiosulfate, sodium polysulfate, potassium sulfite, tetrasodium ethylenediaminetetraacetate, disodium ethylenediaminetetraacetate, sodium nitrilotriacetate, sodium diethylenetriaminepentacarboxylate, sodium hexametaphosphate, sodium triphosphate and calcium bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid monoethyl ester). Selecting the above raw materials as additives can further improve the crystallinity of the polyester. More preferably, the metal salt is selected from at least one of sodium sulfite, tetrasodium ethylenediaminetetraacetate, disodium diaminetetraacetate and calcium bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid monoethyl ester). By optimizing the types of metal salts, the melting crystallization temperature range can be further widened to improve the crystallinity of the polyester.
[0040] In some embodiments, the catalyst is selected from at least one of ethylene glycol antimony, antimony acetate, antimony trioxide and germanium oxide. The catalyst may be any one or more of the above, and all of them can promote the polymerization reaction.
[0041] Furthermore, in the total amount of terephthalic acid and ethylene glycol, the mass proportion of terephthalic acid is 57.3-72.2%, such as 57.3%, 60.0%, 63.0%, 65.0%, 68.0%, 70.0%, 72.2% and the like; the mass proportion of ethylene glycol is 27.8%-42.7%, such as 27.8%, 30.0%, 32.0%, 35.0%, 37.0%, 40.0%, 42.7% and the like, and the sum of terephthalic acid and ethylene glycol is 100%.
[0042] Further, the amount of the catalyst added is 10ppm-300ppm of the total amount of terephthalic acid and ethylene glycol, such as 10ppm, 30ppm, 50ppm, 80ppm, 100ppm, 120ppm, 150ppm, 180ppm, 200ppm, 230ppm, 250ppm, 280ppm, 300ppm, etc. The amount of the metal salt added is 1ppm-500ppm of the mass of terephthalic acid, such as 1ppm, 5ppm, 10ppm, 50ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, etc.
[0043] Further, when the metal salt is a phosphonate, the addition amount is 20ppm-200ppm of the mass of terephthalic acid, such as 20ppm, 50ppm, 80ppm, 100ppm, 130ppm, 150ppm, 180ppm, 200ppm, etc.; when the metal salt is a sulfite, the addition amount is 1ppm-50ppm of the mass of terephthalic acid, such as 1ppm, 5ppm, 10ppm, 15ppm, 20ppm, 25ppm, 30ppm, 35ppm, 40ppm, 45ppm, 50ppm, etc.; when the metal salt is an aminoacetate, the addition amount is 5ppm-150ppm of the mass of terephthalic acid, such as 5ppm, 10ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 110ppm, 120ppm, 130ppm, 140ppm, 150ppm, etc. By adjusting the dosage of different metal salts, different types of metal salts can play a better role, thereby widening the melting crystallization temperature range and achieving saturation of the polyester crystallinity.
[0044] In order to better dissolve the metal salt, the metal salt may be dissolved before adding the metal salt. The metal salt is first mixed and dissolved with a solvent to obtain a metal salt solution before adding, and is added in the form of a metal salt solution.
[0045] In some embodiments, the mass fraction of the metal salt in the metal salt solution is 0.01%-0.5%, such as 0.01%, 0.05%, 0.10%, 0.20%, 0.30%, 0.40%, 0.50%, etc. The solvent is selected from at least one of ethylene glycol and water, and the type of solvent can be any one or more of the above, all of which can dissolve the metal salt well. The metal salt is dispersed in the above solvent, and the dispersion method is not limited, and can be dispersed uniformly at 25°C-120°C by ultrasonic or mechanical stirring.
[0046] S2. Esterification reaction
[0047] The terephthalic acid, ethylene glycol and catalyst are mixed for esterification reaction to obtain an esterified product and enter the next reaction stage. The metal salt is added before the esterification reaction or after the esterification reaction and before the prepolymerization reaction, that is, the metal salt can be added together with the terephthalic acid, ethylene glycol and catalyst, or it can be mixed with the esterified product after the esterification reaction to enter the subsequent prepolymerization reaction stage.
[0048] In some embodiments, the reaction temperature of the esterification reaction is 240°C-270°C, the esterification pressure is 90KPa-120KPa, and the reaction time is 2h-3h. Terephthalic acid, ethylene glycol and a catalyst are mixed and slurried, and the esterification temperature, pressure and other parameters are adjusted to allow the reaction to proceed fully. The reaction process can be carried out in a process tower, and the tower top temperature of the process tower is controlled to be 100°C-120°C. During the reaction, water vapor overflows from the bottom of the tower, and ethylene glycol can be prevented from being taken out within this temperature range. The temperature at the bottom of the tower is not limited, such as 160°C-180°C.
[0049] Specifically, the reaction temperature of the esterification reaction can be 240°C, 245°C, 250°C, 255°C, 260°C, 265°C, 270°C, etc.; the esterification pressure can be 90KPa, 95KPa, 100KPa, 105KPa, 110KPa, 115KPa, 120KPa, etc.; the reaction time can be 2.0h, 2.5h, 3.0h, etc.; the top temperature of the process tower can be 100°C, 105°C, 110°C, 115°C, 120°C, etc.
[0050] S3. Prepolymerization
[0051] The prepolymerization reaction is to further heat the esterified product (bis(hydroxyethyl) terephthalate) - BHET) obtained after esterification and reduce the pressure, so that BHET undergoes ester exchange to generate polymers. By reducing the pressure, the ethylene glycol exchanged during the ester exchange process is extracted, promoting the forward ester exchange reaction.
[0052] In some embodiments, during the prepolymerization reaction, the reaction temperature is controlled to be 250°C-270°C, and the esterification pressure from the esterification reaction is controlled to gradually decrease to 3KPa-5KPa, and the pressure decrease time is 50min-80min. The prepolymerization reaction is fully carried out by regulating the reaction temperature, pressure reduction time and pressure reduction amplitude of the prepolymerization.
[0053] Specifically, during the prepolymerization reaction, the reaction temperature can be 250°C, 255°C, 260°C, 265°C, 270°C, etc.; the pressure after gradually reducing the pressure from the esterification pressure of the esterification reaction (such as 100KPa) can be 3.0KPa, 3.5KPa, 4.0KPa, 4.5KPa, 5.0KPa, etc.; the time used for the pressure drop can be 50min, 55min, 60min, 65min, 70min, 75min, 80min, etc.
[0054] S4. Polycondensation
[0055] After the prepolymerization reaction is completed, the temperature is continued to be raised and the pressure is reduced to carry out the polycondensation reaction so that the reaction is fully completed.
[0056] In some embodiments, the reaction temperature of the polycondensation reaction is 275°C-280°C, such as 275°C, 276°C, 277°C, 278°C, 279°C, 280°C, etc.; the reaction pressure of the polycondensation reaction is 10Pa-100Pa, such as 10Pa, 20Pa, 30Pa, 40Pa, 50Pa, 60Pa, 70Pa, 80Pa, 90Pa, 100Pa, etc.; the reaction time of the polycondensation reaction is 1h-2h, such as 1.0h, 1.5h, 2.0h, etc. The stirring frequency can be 25Hz-50Hz, such as 25Hz, 30Hz, 35Hz, 40Hz, 45Hz, 50Hz, etc.
[0057] S5, solid phase viscosity enhancement
[0058] After the polycondensation reaction is completed, the polyester chips are pelletized and dried to obtain polyester chips, and then the polyester chips are solid-phase thickened to make the intrinsic viscosity reach the target viscosity to obtain saturated crystalline PET polyester. The target viscosity can be 0.9dL / g-1.3dL / g, such as 0.9dL / g, 1.0dL / g, 1.1dL / g, 1.2dL / g, 1.3dL / g, etc.
[0059] In some embodiments, the solid phase viscosity increasing process is carried out in a rotary drum solid phase viscosity increasing device, and the temperature of the solid phase viscosity increasing is controlled to be 220°C-230°C, the pressure is 10Pa-100Pa, and the solid phase viscosity increasing time is 30h-45h, and the polyester is fully crystallized by adjusting the operating parameters of the solid phase viscosity increasing. Specifically, the temperature of the solid phase viscosity increasing can be 220°C, 223°C, 225°C, 228°C, 230°C, etc., the pressure can be 10Pa, 30Pa, 50Pa, 80Pa, 100Pa, etc., and the solid phase viscosity increasing time can be 30h, 33h, 35h, 38h, 40h, 43h, 45h, etc.
[0060] The embodiment of the present invention also provides a PET polyester, which is obtained by polymerization of terephthalic acid, ethylene glycol, a catalyst and a metal salt as raw materials. The specific steps can refer to the above preparation method. By adding an auxiliary agent, the high-viscosity polyester reaches saturated crystallinity during the melt crystallization process, and solves the problems of stability, mechanical strength or surface smoothness of the product, etc., which may cause the high-viscosity polyester to be shortened after processing.
[0061] The intrinsic viscosity of the PET polyester provided in the embodiment of the present invention is 0.9 dL / g-1.3 dL / g, and has the characteristic of high viscosity.
[0062] Since the PET polyester prepared in the embodiment of the present invention reaches saturated crystallinity, the PET polyester is heated to 280-320°C to eliminate the thermal history, undergoes melt crystallization, and is heated again to melt. The melting process has no cold crystallization peak or the cold crystallization enthalpy is very small. When the cold crystallization peak appears, the cold crystallization enthalpy is 0J / g-3J / g.
[0063] The PET polyester provided in the embodiment of the present invention has reached saturated crystallinity and has a very good molding effect, and can be further used to prepare plastic products, thereby improving the stability of the plastic products.
[0064] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0065] Example 1
[0066] This embodiment provides a method for preparing PET polyester, the steps are as follows:
[0067] (1) Weigh 0.073 g of metal salt (sodium sulfite) and dissolve it in 50 g of ethylene glycol, and disperse it by ultrasonic at room temperature for 5 min.
[0068] (2) Weigh 3.46 kg of ethylene glycol, 7.75 kg of terephthalic acid, and 3.21 g of ethylene glycol antimony, place them in a 20 L polymerization apparatus, heat to 80° C. and beat for 20 min (the amount of metal salt added in this example is 9.4 ppm of the mass of terephthalic acid).
[0069] (3) The kettle temperature was raised to 246°C, the pressure was controlled at 100-110 kPa, the process tower top temperature was controlled at 105°C-110°C, and esterification was started, and the reaction time was controlled to 106 min. When the amount of esterified water collected reached more than 97% of the theoretical amount (1.66 kg of esterified water was collected), and the esterified water no longer distilled out, the esterification was terminated.
[0070] (4) Add metal salt-ethylene glycol solution into the reactor.
[0071] (5) Prepolymerization was started. The prepolymerization temperature was slowly increased from 252°C to 269°C. The heating time was 52 minutes. The prepolymerization pressure was linearly decreased from 100 KPa to 3 KPa by program control. The decreasing process time was 60 minutes.
[0072] (6) The final polymerization temperature was controlled at 278°C, the stirring frequency was controlled at 40 Hz, the pressure was controlled at <100 Pa, the reaction time was 107 min, the material was discharged, pelletized, dried, and weighed 7.65 kg.
[0073] (7) The dried polyester chips were placed in a 50L drum and heated under program control. After sufficient crystallization, the temperature was raised to 225-226.3°C for solid phase viscosity enhancement. The drum pressure was controlled to be less than 15 Pa, and the viscosity enhancement time was 36 h.
[0074] Example 2
[0075] This embodiment provides a method for preparing PET polyester, which is substantially the same as the steps in Embodiment 1, except for the following parameters:
[0076] In step (1), the metal salt is 0.47 g of tetrasodium ethylenediaminetetraacetate.
[0077] In step (3), the esterification temperature was 245-247.5°C for 111 min, and 1.67 kg of esterification water was collected.
[0078] In step (5), the prepolymerization temperature is 250°C to 269°C, and the heating time is 51 minutes.
[0079] In step (6), the final polymerization temperature is 275-278.5° C., the reaction time is 110 min, the material is discharged, pelletized, dried, and weighed 7.23 kg.
[0080] In step (7), the drum viscosity increasing temperature is between 225 and 226.8° C., the drum pressure is less than 15 Pa, and the viscosity increasing time is 36 hours.
[0081] Example 3
[0082] This embodiment provides a method for preparing PET polyester, which is substantially the same as the steps in Embodiment 1, except for the following parameters:
[0083] In step (1), weigh 0.35 g of disodium ethylenediaminetetraacetate.
[0084] In step (3), esterification was carried out at 245-247.5°C for 109 min, and 1.67 kg of esterification water was collected.
[0085] In step (5), the prepolymerization temperature is 250°C to 269°C, and the heating time is 53 minutes.
[0086] In step (6), the final polymerization reaction temperature is 275-278.9°C, the reaction time is 105 min, the material is discharged, pelletized, dried, and weighed 7.62 kg.
[0087] In step (7), the drum viscosity increasing temperature is between 225 and 226.4° C., the drum pressure is less than 15 Pa, and the viscosity increasing time is 36 hours.
[0088] Example 4
[0089] This embodiment provides a method for preparing PET polyester, which is substantially the same as the steps in Embodiment 1, except for the following parameters:
[0090] In step (1), 0.49 g of calcium bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonate) was weighed.
[0091] In step (3), esterification was carried out at 245-249.1°C for 97 min, and 1.67 kg of esterification water was collected.
[0092] In step (5), the prepolymerization temperature is 253° C. to 269° C., and the heating time is 49 minutes.
[0093] In step (6), the final polymerization reaction temperature is 275-278.3°C, the reaction time is 99 min, the material is discharged, pelletized, dried, and weighed 7.77 kg.
[0094] In step (7), the drum viscosity increasing temperature is between 225 and 226.3° C., the drum pressure is less than 15 Pa, and the viscosity increasing time is 36 hours.
[0095] Example 5
[0096] The only difference from Example 1 is that the type of metal salt in step (1) is replaced by an equal amount of sodium diethylenetriamine pentacarboxylate.
[0097] Example 6
[0098] The only difference from Example 1 is that the type of metal salt in step (1) is replaced by an equal amount of calcium bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonate).
[0099] Example 7
[0100] The only difference from Example 1 is that the type of metal salt in step (1) is replaced by an equal amount of sodium nitrilotriacetate.
[0101] Example 8
[0102] The only difference from Example 1 is that the amount of metal salt used in step (1) is 0.033 g, and the amount of metal salt added in this example is 4.25 ppm based on the mass of terephthalic acid.
[0103] Example 9
[0104] The only difference from Example 1 is that the amount of metal salt used in step (1) is 0.155 g, and the amount of metal salt added in this example is 20 ppm based on the mass of terephthalic acid.
[0105] Comparative Example 1
[0106] This comparative example provides a method for preparing PET polyester, which is substantially the same as the steps in Example 1, except for the following parameters:
[0107] In step (1), a blank sample is prepared without adding metal salt.
[0108] In step (4), 50 g of ethylene glycol was added.
[0109] Comparative Example 2
[0110] This comparative example provides a method for preparing PET polyester, which is substantially the same as the steps in Example 1, except for the following parameters:
[0111] In step (1), weigh 0.52 g of sodium benzoate (nucleating agent).
[0112] In step (3), esterification was carried out at 245-249.7°C for 105 min, and 1.67 kg of esterification water was collected.
[0113] In step (4), sodium benzoate ethylene glycol solution is added.
[0114] In step (5), the prepolymerization temperature is 251° C. to 269° C., and the heating time is 53 min.
[0115] In step (6), the final polymerization reaction temperature is 275-278.6°C, the reaction time is 106 min, the material is discharged, pelletized, dried, and weighed 8.17 kg.
[0116] In step (7), the drum viscosity increasing temperature is between 225 and 226.2° C., the drum pressure is less than 15 Pa, and the viscosity increasing time is 36 hours.
[0117] Test Example 1
[0118] The properties of the polyester chips prepared in the test examples and comparative examples are shown in Table 1.
[0119] Test method: The test methods for intrinsic viscosity, terminal carboxyl group and color value refer to GB / T 14190-2017.
[0120] Table 1 Examples and Comparative Examples Formulas and Polyester Chip Parameters
[0121]
[0122] Judging from the basic parameters of the polyester chips, the viscosity and terminal carboxyl groups are basically at the same level and can be compared.
[0123] Test Example 2
[0124] The DSC curves of the polyester chips prepared in the test examples and comparative examples are subjected to the elimination of thermal history. Figure 1 is the melting crystallization curve, Figure 2 This is the melting curve of heating again.
[0125] Test method: According to GB / T 14190-2017
[0126] (1) Melting and crystallization curve test: after eliminating the thermal history, reduce the temperature from 280°C to 40°C at a rate of 10°C / min; (2) Reheating melting curve test: after melting and crystallization, increase the temperature from 40°C to 280°C at a rate of 10°C / min.
[0127] Figure 2 It can be seen that the curves of Examples 1-4, 7, and 9 are all straight lines, without cold crystallization behavior, indicating that the melt crystallization process is relatively complete and the degree of crystallinity has reached saturation; Examples 5, 6, and 8 have a slowing effect due to the type and dosage. After the metal salt dosage of Examples 5 and 6 remains unchanged and the type is changed, the cold crystallization peak shows slight fluctuations, while Example 7 is completely straight, indicating that different metal salts have their corresponding addition amounts; when the metal salt addition amount of Example 8 is low, the cold crystallization peak appears slightly, while in Example 9, when the metal salt addition amount is high, the cold crystallization peak is straight, indicating that the addition amount affects the cold crystallization peak; Comparative Examples 1 and 2 both have cold crystallization peaks, indicating that there is recrystallization during the heating and melting process, indicating that in the melt crystallization process, some areas have not reached complete crystallization and the crystallinity is unsaturated. Obviously, this recrystallization phenomenon is not good for the dimensional stability and smoothness of PET products.
[0128] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A PET polyester, characterized in that: It is obtained by polymerization using terephthalic acid, ethylene glycol, catalyst and metal salt as raw materials; Wherein, the metal salt is selected from at least one of phosphonate, sulfite and aminoacetate.
2. The PET polyester according to claim 1, characterized in that In the total amount of terephthalic acid and ethylene glycol, the mass proportion of terephthalic acid is 57.3%-72.2%, and the mass proportion of ethylene glycol is 27.8%-42.7%; Preferably, the catalyst is added in an amount of 10ppm-300ppm based on the total amount of terephthalic acid and ethylene glycol; Preferably, the added amount of the metal salt is 1 ppm-500 ppm based on the mass of terephthalic acid.
3. The PET polyester according to claim 1 or 2, characterized in that The metal salt is selected from at least one of sodium sulfite, sodium bisulfite, sodium thiosulfate, sodium polysulfate, potassium sulfite, tetrasodium ethylenediaminetetraacetate, disodium ethylenediaminetetraacetate, sodium nitrilotriacetate, diethylenetriamine pentacarboxylate, sodium hexametaphosphate, sodium triphosphate and calcium bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonate); Preferably, the metal salt is selected from at least one of sodium sulfite, tetrasodium ethylenediaminetetraacetate, disodium diaminetetraacetate, and calcium bis(3,5-di-tert-butyl-4-hydroxybenzylphosphonate); Preferably, when the metal salt is a phosphonate, the added amount is 20ppm-200ppm of the mass of terephthalic acid; when the metal salt is a sulfite, the added amount is 1ppm-50ppm of the mass of terephthalic acid; when the metal salt is an aminoacetate, the added amount is 5ppm-150ppm of the mass of terephthalic acid; Preferably, the catalyst is selected from at least one of antimony glycol, antimony acetate, antimony trioxide and germanium oxide.
4. The PET polyester according to claim 1, characterized in that The intrinsic viscosity of the PET polyester is 0.9dL / g-1.3dL / g; Preferably, the PET polyester is heated to 280-320°C to eliminate the thermal history, undergoes melt crystallization, and is heated again to melt. The melting process has no cold crystallization peak or a small cold crystallization enthalpy. When a cold crystallization peak appears, the cold crystallization enthalpy is 0 J / g-3 J / g.
5. A method for preparing the PET polyester according to any one of claims 1 to 4, characterized in that: include: The polymerization is carried out with terephthalic acid, ethylene glycol, a catalyst and a metal salt as raw materials, followed by solid phase adhesion.
6. The preparation method according to claim 5, characterized in that: The preparation process includes esterification reaction, prepolymerization reaction, polycondensation reaction and solid phase viscosity enhancement in sequence; Wherein, the metal salt is added before the esterification reaction or after the esterification reaction and before the prepolymerization reaction; Preferably, the metal salt is mixed and dissolved with a solvent to obtain a metal salt solution before being added, and is added in the form of the metal salt solution; more preferably, the mass fraction of the metal salt in the metal salt solution is 0.01%-0.5%; more preferably, the solvent is selected from at least one of ethylene glycol and water.
7. The preparation method according to claim 6, characterized in that: The esterification reaction comprises: mixing terephthalic acid, ethylene glycol and a catalyst to carry out an esterification reaction to obtain an esterified product; The reaction temperature of the esterification reaction is 240° C.-270° C., the esterification pressure is 90 KPa-120 KPa, the top temperature of the process tower is controlled to be 100° C.-120° C., and the reaction time is 2h-3h.
8. The preparation method according to claim 6, characterized in that: During the prepolymerization reaction, the reaction temperature is controlled to be 250° C.-270° C., and the esterification pressure of the esterification reaction is controlled to gradually decrease to 3KPa-5KPa, and the time for the pressure decrease is 50min-80min.
9. The preparation method according to claim 6, characterized in that: The reaction temperature of the polycondensation reaction is 275°C-280°C, the reaction pressure is 10Pa-100Pa, and the reaction time is 1h-2h; Preferably, after the polycondensation reaction is completed, the polyester chips are pelletized and dried to obtain polyester chips, and then the polyester chips are solid-phase thickened to make the intrinsic viscosity reach 0.9 dL / g-1.3 dL / g; Preferably, the solid phase viscosity increasing process is carried out in a rotary drum solid phase viscosity increasing device, and the temperature of the solid phase viscosity increasing is controlled to be 220° C.-230° C., the pressure is 10 Pa-100 Pa, and the solid phase viscosity increasing time is 30 h-45 h.
10. Use of the PET polyester according to any one of claims 1 to 4 or the PET polyester prepared by the preparation method according to any one of claims 5 to 9 in the preparation of plastic products.